THE CULTURAL ADAPTATION PROCESS OF INDONESIAN STUDENTS STUDYING IN GERMANY - Nico Prakasa Anandadea; Amelberga Astuti (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2024)
Technological advancements facilitate Indonesian students to continue their studies abroad such as in Germany. Various benefits can be obtained, such as self-development. However, cultural differences namely language and characteristics of society can cause barriers in intercultural communication. This research examines the adaptation process of Indonesian students studying in Germany. The method used is descriptive qualitative with in-depth interviews. The theories used are Communication Accommodation and U Curve Theory. The research results show that the students went through the four phases of the U Curve Theory, and they have the same strategy in dealing with cultural differences.